1998
DOI: 10.1088/0031-9155/43/8/002
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo study of the quality dependence factors of common TLD materials in photon and electron beams

Abstract: A Monte Carlo simulation of the quality dependence of different TL materials, in the form of discs 3.61 mm in diameter and 0.9 mm thick, in radiotherapy photon beams relative to 60Co gamma-rays has been performed. The beam qualities ranged from 50 kV to 25 MV x-rays. The TL materials were: CaF2, CaSO4, LiF and Li2B4O7. The effects of the dopants on energy deposition in the TL material have also been determined for the highly sensitive LiF:Mg:Cu:P (TLD-100H) and for CaF2:Mn. It was found that there was a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 28 publications
(47 reference statements)
4
30
1
Order By: Relevance
“…In dosimetry it is frequently assumed that the quality dependence of thermonuminescence LiF:Mg,Ti detectors such as TLD-100, follows the ratio of the energy absorption coefficient for the LiF and water. It has been shown by Mobit et al (1998), that the quality dependence factor for LiF-TLD in kilovoltage x-rays relative to 60 C 0 gamma-rays ranges from 1.36 for 50 kV x-rays to 1.03 for 300 kV which are comparable with our results [10]. Kearfott et al (1990) observed an quality dependence factor of LiF TL ribbon from 1.045 (50 keV) to 1.353 (100 keV) [12].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In dosimetry it is frequently assumed that the quality dependence of thermonuminescence LiF:Mg,Ti detectors such as TLD-100, follows the ratio of the energy absorption coefficient for the LiF and water. It has been shown by Mobit et al (1998), that the quality dependence factor for LiF-TLD in kilovoltage x-rays relative to 60 C 0 gamma-rays ranges from 1.36 for 50 kV x-rays to 1.03 for 300 kV which are comparable with our results [10]. Kearfott et al (1990) observed an quality dependence factor of LiF TL ribbon from 1.045 (50 keV) to 1.353 (100 keV) [12].…”
Section: Discussionsupporting
confidence: 91%
“…Monte Carlo calculation did not show any difference in behaviour of pure LiF and TLD-100 in kilovoltage or megavoltage x-ray ranges. This is expected since the concentration of Ti and Mg by weight is negligible in TLD-100 [10]. The TLD chips were represented by 3.1 mm ×3.1 mm×1 mm.…”
Section: Monte Carlo Simulationmentioning
confidence: 96%
“…The generation of a separate calibration factor (RCF) for each beam quality improved the overall result compared to a single calibration factor. No correction factors derived from published models 26 were applied in this work. The TLDs were also given a known absorbed dose in the 300 kV p therapy beam and then read using the RCF of the 180 kV p therapy beam.…”
Section: Tld Calibration Results At the Simulatormentioning
confidence: 99%
“…In some cases, the use of monoenergetic photon beams along with mathematical models have been employed to predict the energy dependence of TLD response 23,24 . Correction factors for different beam qualities have also been generated to compensate for this effect 26 . According to Kron et al 23 , variation in TLD response could be due to the assumption that the response at low energies reduces exponentially whereas at medium energies, it varies according to the energy dependence from the photoelectric effect.…”
Section: Tld Calibration Results At the Simulatormentioning
confidence: 99%
“…Mobit et al [11] performed Monte Carlo study of the quality dependence of LiF TLD in kilovoltage photon beams for radiotherapy dosimetry studies. Kearfott et al [12] observed an energy response of LiF TL ribbon for low energy x-rays.…”
Section: Introductionmentioning
confidence: 99%